Estymacja pośrednia jako metoda szacowania informacji o działalności gospodarczej dla małych przedsiębiorstw w przekroju domen - Klimanek, Tomasz (Indirect estimation of small business characteristics, 2006)
The Polish economic statistics faced a serious challenge in the nineties of the last century. That was because of a rapid change in the structure of enterprises, widening of the area the shadow economy and the increasing demand for the information on small territorial area and branch cross-section. Then quite new challenges emerged: the access to new alternative sources of data, improvement as far as data processing is concerned, and new estimation techniques. Based on the experiences of the EURAREA project, the paper presents an attempt to use small area statistics methods to improve estimation precision with respect to basic information about economic activities of small business. The study was aimed at accounting for and applying tax data for a more effective use of a sample survey of small businesses with up to 9 employees. The domains were defined as voivodship and PKD category cross-section and the estimates for them were produced by the use of synthetic regression estimator. The final part of the paper focuses on the quality of estimation discussed from two perspectives: efficiency and bias.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 154-166